Analisis Pengaruh Kepuasan terhadap Loyalitas Tamu pada Departemen Food and Beverage Service Fahira Hotel Bukittinggi - Putri Nadira; Jon Kenedi (Lembaga Yasin AlSys, 2025)
This study aims to identify the effect of satisfaction levels on guest loyalty toward the services provided by the Food and Beverage Department at Hotel Fahira Bukittinggi. The research is grounded in the importance of understanding customer satisfaction and loyalty dynamics as key indicators of service success in the hospitality industry. A quantitative approach with a correlational design was employed. Data were collected through a survey using questionnaires distributed to 32 hotel guests and analyzed through several stages, including instrument testing, classical assumption testing, simple linear regression analysis, t-test, and determination coefficient (R²) calculation. The analysis revealed that satisfaction significantly affects guest loyalty; however, the relationship is negative, with a regression coefficient of -2.731. This indicates that higher satisfaction is paradoxically associated with lower guest loyalty. The R² value of 0.451 shows that satisfaction accounts for 45.1% of the variation in loyalty, while the remaining 54.9% is influenced by other external factors beyond the scope of this study. These findings suggest the need for further investigation into other dimensions that may mediate or moderate the relationship between satisfaction and loyalty in the context of hotel food and beverage services.